Aphid‐parasitoids trophic relationship in a cereal crop succession system: Population oscillation and food webs. (28th May 2022) - dos Santos, Carlos Diego Ribeiro; Lau, Douglas; Redaelli, Luiza Rodrigues; Jahnke, Simone Mundstock; Pereira, Paulo Roberto Valle da Silva; Engel, Eduardo; Sampaio, Marcus Vinicius
Abstract: In the 1970s, cereal aphids populations (specially Metopolophium dirhodum ) were out of balance in the subtropical region of South America and a successful biological control program with the introduction of parasitoids restored equilibrium. After that, changes in crop systems may have affected aphid‐parasitoid communities. The objective of this work was to evaluate the current assemblage of cereal aphid parasitoids, describing their oscillations, parasitism level, and trophic relationships in food webs in a cereal succession system (wheat‐corn‐oat) currently adopted in this region. Over a year, the associated parasitoid/hyperparasitoid species were inventoried by field‐exposed Rhopalosiphum padi, Schizaphis graminum, M. dirhodum, and Sitobion avenae (recruitment method) and by Moericke traps. Six species of primary parasitoids were sampled in both aphids and traps with the same abundance sequence: A. platensis, A. rhopalosiphi, L. testaceipes, D. rapae, A. uzbekistanicus, and A. ervi . Parasitism and complexity of food webs were higher during the wheat season (winter–spring), decreasing in corn (summer) and increasing again in oat (autumn). In the current assemblage of cereal aphid parasitoids in the subtropical region of South America, three species of parasitoids that were already present before the biological control program and three that were introduced oscillate in abundance throughout the year, resulting in an alternation of the complexity of the food webs and in the levels of parasitism in the crop seasons. A. platensis and A. rhopalosiphi are the most abundant species and A. rhopalosiphi remains fundamental in the control of M. dirhodum and S. avenae .